Metagenomic and Transcriptomic Analyses Reveal the Differences and Associations Between the Gut Microbiome and Muscular Genes in Angus and Chinese Simmental Cattle - Zheng, Ya; Chen, Juanjuan; Wang, Xiaoxuan; Han, Ling; Yang, Yayuan; Wang, Qi; Yu, Qunli (Frontiers in Microbiology, 2022)
Gut microbiome and heredity are two important factors affecting the intramuscular fat (IMF) of cattle, excluding age, sex, and nutrition. This study aimed at deciphering these two differences by analyzing the gut microbiome and intramuscular differentially expressed genes (DEGs) in the Angus and Chinese Simmental cattle. Feces and longissimus dorsi were collected from the two groups of animals (n = 20/group) for multiomics analysis. Angus holds a significantly higher diversity than Chinese Simmental, and the relative abundance of Roseburia, Prevotella, Coprococcus, etc., was obviously higher in Angus. Chinese Simmental had higher levels of isobutyrate, isovalerate, and valerate, although similar levels of acetate, propionate, and butyrate were observed for the two groups. The DEGs upregulated in Chinese Simmental were mainly involved in immune and inflammatory responses, while those in Angus were associated with the regulation of muscle system and myofibril. We finally identified 17 species, including Eubacterium rectale, etc., which were positively correlated to muscle and fat metabolism genes (MSTN, MYLPF, TNNT3, and FABP3/4) and illustrate the associations between them. Our study unveils the gut microbial differences and significant DEGs as well as their associations between the two breeds, providing valuable guidance for future mechanism research and development of intervention strategies to improve meat quality.